• 2022-05-29
    已知(t)=δ(t-1),(t)=ε(t-2),则(t)*(t)的值是()
    A: ε(t)
    B: ε(t-1)
    C: ε(t-2)
    D: ε(t-3)
  • D

    内容

    • 0

      已知信号x(t)如图所示,其表达式为()。 A: u(t)+2u(t-2)-u(t-3) B: u(t-1)+u(t-2)-2u(t-3) C: u(t)+u(t-2)-u(t-3) D: u(t-1)+u(t-2)-u(t-3)

    • 1

      用下列差分方程描述的系统为线性系统的是( )。 A: y(t)+y(t-1)=2f(t)+3 B: y(t)+y(t-1)y(t-2)=2f(t) C: y(t)+ty(t-2)=f(1-t)+2f(t-1) D: y(t)+2y(t-2)=2|f(t)|

    • 2

      用阶跃函数表示图中所示函数f(t)等于()。 A: f(t)=ε(t)+2ε(t-1)-ε(t-3)-ε(t-4) B: f(t)=2ε(t-1)-ε(t-3)-ε(t-4) C: f(t)=ε(t)+ε(t-1)-ε(t-3)-ε(t-4) D: f(t)=ε(t-1)-ε(t-3)-ε(t-4)

    • 3

      已知f(t)=u(t-1)-u(t-2),且s(t)=f(t)*f(t),则s(3)=? <br/>______

    • 4

      用阶跃函数表示图中所示函数f(t)等于()。[img=300x226]17da6afdcdea4ea.png[/img] A: f(t)=ε(t)+2ε(t-1)-ε(t-3)-ε(t-4) B: f(t)=2ε(t-1)-ε(t-3)-ε(t-4) C: f(t)=ε(t)+ε(t-1)-ε(t-3)-ε(t-4) D: f(t)=ε(t-1)-ε(t-3)-ε(t-4)